La trascendencia constitucional de la neutralidad de red - Fernández Baca, Dilmar Villena (Pontificia Universidad Católica del Perú, 2016)
New technologies have transformed the traditional ways in which people develop and express themselves. In that context, the internet has meant a revolution in different spheres of society, in which the users and network providers are developed. Faced with this, the question arises: Should the relations that are presented in the network be regulated?.In this article, the author develops the principle of net neutrality as the basis of the protection of the fundamental rights from the different agents that are related by this means. It will be exposed the current regulation of the matter and its scope, which finds its support in the constitutional regulation.

Las nuevas tecnologías han transformado las formas tradicionales en las que se desarrollan y expresan las personas. En ese contexto, internet ha significado una revolución en diferentes ámbitos de la sociedad, en los cuales los usuarios y proveedores de la red se desenvuelven. Ante ello, surge la interrogante: ¿deben regularse las relaciones que se presentan en la red?.En el presente artículo, el autor desarrolla el principio de neutralidad de la red como base de la protección de los derechos fundamentales de los diferentes agentes que se relacionan por este medio. Se expondrá la regulación vigente de la materia y sus alcances, la cual encuentra su sustento en la regulación constitucional.
The constitutional transcendence of net neutrality
Keywords: Derecho; https://purl.org/pe-repo/ocde/ford#5.05.01